Optimalisasi pembelajaran menggunakan media berbasis TIK - Miftah, Mohamad (Educenter : Jurnal Ilmiah Pendidikan, 2022)
Media for teachers is an important tool in delivering teaching materials. The ability to design and develop integrated media in learning is the capital of successful learning. The purpose of the research is to share ideas that teacher learning activities are required to reduce the use of the lecture method and can be enriched by the use of learning media, the role of learning media is becoming increasingly important. The research method is literature review. The results of the research that ICT is a program, for tools, manipulation and conveying information. The presence of media in the learning process really helps make it easier for students to better understand the subject. In addition, teachers or learners need to do careful planning when designing learning in the classroom.